Health literacy and informed consent for clinical trials: a systematic review and implications for nurses - Burks AC; Keim-Malpass J (Dove Medical Press, 2019)
Allison C Burks, Jessica Keim-MalpassDepartment of Acute and Specialty Care, University of Virginia School of Nursing, Charlottesville, VA, USAAbstract: The informed consent process for consideration of clinical trials is a complex process that requires the understanding of the potential trial risk, benefits, and alternatives of treatment. The aim of this systematic review was to explore the available literature related to health literacy and the informed consent process for clinical trials. Articles were included if they focused on health literacy and patient comprehension of informed consent, had perceptions related to the informed consent process, or assessed the impact of health literacy on patients’ willingness to participate in clinical trials. Eight articles were selected for this review. Limited health literacy was determined to be related to a lack of comprehension of clinical trial consent documents and heightened anxiety surrounding the informed consent process. Conflicting evidence exists around the relationship between health literacy and clinical trial enrollment. Limited health literacy levels may impact the ability for nurses to have effective informed consent processes.Keywords: health literacy, clinical trial participation, clinical trial enrollment disparity, clinical trial consent